ANALISIS PERTUMBUHAN EKONOMI DALAM MENUNJANG PEMBANGUNAN DAERAH DI PROVINSI JAMBI - M Zahari MS (Jurnal Ilmiah Universitas Batanghari Jambi, 2012)
Jambi province is a province in Indonesia are quite rich in natural resources, good earth is a result of oil and gas, a new stone, gold and others, as well as the results of the plantation of oil palm, rubber, pineapple, coconut, tea and other sectors. However, the problem of whether natural wealth belonging to the seoptimal might have can be utilized so as to support economic growth in the province of Jambi.This research goal seeking to know the picture of economical progress based on economic growth and income per person on each of the regency / a city in Jambi. An object research is that the entire district / a city in jambi by using data skunder of domestik regional products gross ( PDRB ) and the inhabitants of the district/a city in Jambi 2000-2010. The approach used is descriptive heading for : analysis of economic growth, and analysis klassen typology .This research result explained that economic growth jambi during periods of 2000-2010 continued to increase, with average grew by 6,21 percent. based on analysis of klassen typology, the experiencing self rapidly progressing and fast growing is district Tanjung Jabung Barat. The forward but depressed is district Tanjung Jabung Timur and city Jambi, includes the cities of the full. Classifications developing areas fast was district Sarolangun and Bungo. the region economic growth is relatively lagging Batanghari district , Muaro Jambi, Merangin, Kerinci, and Tebo.